Scientific collection of Paleontology and the communication ability of a blog about the discipline (Terr@ Plural, 2021)
To enhance the teaching of Paleontology, due to the lack of tools to assist it in the undergraduate course in Geology at the Federal University of Uberlândia, Brazil, we developed a blog using the existing resources on a free online platform, as well as additional features developed in HTML, CSS, and JavaScript languages. To accomplish this task, the fossil samples from the Laboratory of Stratigraphic Paleontology (LAPE) of the Federal University of Uberlândia, Monte Carmelo Campus needed to be identified, recorded, grouped according to taxonomic proximity, and analyzed quantitatively and qualitatively. We evaluated the communication capacity of the tool to reach the most diverse readers, according to statistical data provided internally by the platform, highlighting the moment of social distancing caused by the COVID-19 Pandemic.
Keywords: Fossils; Extension; Digital tools